A Case Study on Acupuncture in the Treatment of Schizophrenia. Issue 3 (June 2014) - Bosch, Peggy; Staudte, Heike; van den Noort, Maurits; Lim, Sabina
This report describes the use of acupuncture as an add on treatment for a patient with chronic schizophrenia. The 63-year-old woman suffered from persistent hallucinations and even physical pain as a result of the hallucination of a black bird that kept pecking her back. The patient received 12 weekly acupuncture treatments. A clinical diagnostic interview and psychological testing (on sleep quality, depression, and on positive and negative symptoms) were conducted before, immediately after and 3 months after the acupuncture treatment. The results of the diagnostic interview gave important insights into the treatment effects. The patient experienced improved daily functioning and noticed a change in hallucinations. Although the hallucinations still occurred, she felt less disturbed by them. Interestingly, pain decreased markedly. In addition, the results showed that the overall score of the positive and negative symptoms did not change immediately; however, a decrease in symptoms occurred 3 months after acupuncture treatment. Moreover, the patient described an immediate improvement in sleep; this was confirmed by a daytime sleepiness questionnaire. The patient was not able to complete a (longer) test on sleep quality beforehand but did so after the treatment period. Finally, a delayed improvement in the depression scale was found. Although larger clinical intervention studies on acupuncture and schizophrenia are needed, the results of this case study indicate that acupuncture may be beneficial as an add on treatment tool in patients with schizophrenia. Trial registration number: 3132.